Revisiting the CMB homogeneity scale: low multipoles removal effect and extragalactic foreground masking - Shao, Xiaoyun (2025)
The Cosmic Microwave Background (CMB) reaches homogeneity at relativelymodest angular scales compared to the expectation of the standard ΛCDM model revealingan important challenge to the theoretical predictions. We analyze this inconsistency throughthe homogeneity scale H and the slope of the homogeneity index at θ = 90◦ . We find thatthe removal of low multipoles, in particular the quadrupole, from both the data and theΛCDM synthetic CMB maps, significantly improve the consistency between models andobservations. This adds to indications of the relevant contribution of the low value of theCMB quadrupole to the observed anomalies in the homogeneity scale. Due to the presence ofa new extragalactic foreground in the CMB maps, we have performed statistical analyseswith different masking taking into account the regions mostly affected. In particular weconsider galaxies in the local neighborhood which are expected to affect more significantlythe large angular scales. We find that by masking these regions, the analysis cannot solve thediscrepancy between the observations and the ΛCDM model in spite of a small improvementof their mutual consistency. The studies with both foreground masking and low-ℓ removedCMB maps show similar results than those of the full CMB map indicating that the maindiscrepancy between theory and observations is associated to the quadrupole anomaly andmay require more exhaustive analysis.